Provider performance in treating poor patients - factors influencing prescribing practices in lao PDR: a cross-sectional study - Petzold Max; Tomson Göran; Soukaloun Douangdao; Syhakhang Lamphone; Rehnberg Clas; Wahlström Rolf (BMC, 2011)
Abstract Background Out-of-pocket payments make up about 80% of medical care spending at hospitals in Laos, thereby putting poor households at risk of catastrophic health expenditure. Social security schemes in the form of community-based health insurance and health equity funds have been introduced in some parts of the country. Drug and Therapeutics Committees (DTCs) have been established to ensure rational use of drugs and improve quality of care. The objective was to assess the appropriateness and expenditure for treatment for poor patients by health care providers at hospitals in three selected provinces of Laos and to explore associated factors. Methods Cross-sectional study using four tracer conditions. Structured interviews with 828 in-patients at twelve provincial and district hospitals on the subject of insurance protection, income and expenditures for treatment, including informal payment. Evaluation of each patient's medical record for appropriateness of drug use using a checklist of treatment guidelines (maximum score = 10). Results No significant difference in appropriateness of care for patients at different income levels, but higher expenditures for patients with the highest income level. The score for appropriate drug use in insured patients was significantly higher than uninsured patients (5.9 vs. 4.9), and the length of stay in days significantly shorter (2.7 vs. 3.7). Insured patients paid significantly less than uninsured patients, both for medicines (USD 14.8 vs. 43.9) and diagnostic tests (USD 5.9 vs. 9.2). On the contrary the score for appropriateness of drug use in patients making informal payments was significantly lower than patients not making informal payments (3.5 vs. 5.1), and the length of stay significantly longer (6.8 vs. 3.2), while expenditures were significantly higher both for medicines (USD 124.5 vs. 28.8) and diagnostic tests (USD 14.1 vs. 7.7). Conclusions The lower expenditure for insured patients can help reduce the number of households experiencing catastrophic health expenditure. The positive effects of insurance schemes on expenditure and appropriate use of medicines may be associated with the long-term effects of promoting rational use of drugs, including support to active DTC work.